N‐Terminal PreS1 Sequence Regulates Efficient Infection of Cell‐Culture–Generated Hepatitis B Virus. Issue 2 (31st October 2020) - Murayama, Asako; Yamada, Norie; Osaki, Yoshiki; Shiina, Masaaki; Aly, Hussein Hassan; Iwamoto, Masashi; Tsukuda, Senko; Watashi, Koichi; Matsuda, Mami; Suzuki, Ryosuke; Tanaka, Tomohisa; Moriishi, Kohji; et al.
Abstract : Background and Aims: An efficient cell‐culture system for hepatitis B virus (HBV) is indispensable for research on viral characteristics and antiviral reagents. Currently, for the HBV infection assay in cell culture, viruses derived from HBV genome‐integrated cell lines of HepG2.2.15 or HepAD‐38 are commonly used. However, these viruses are not suitable for the evaluation of polymorphism‐dependent viral characteristics or resistant mutations against antiviral reagents. HBV obtained by the transient transfection of the ordinary HBV molecular clone has limited infection efficiencies in cell culture. Approach and Results: We found that an 11‐amino‐acid deletion (d11) in the preS1 region enhances the infectivity of cell‐culture–generated HBV (HBVcc) to sodium taurocholate cotransporting polypeptide–transduced HepG2 (HepG2/NTCP) cells. Infection of HBVcc derived from a d11‐introduced genotype C strain (GTC‐d11) was 10‐fold more efficient than infection of wild‐type GTC (GTC‐wt), and the number of infected cells was comparable between GTC‐d11‐ and HepG2.2.15‐derived viruses when inoculated with the same genome equivalents. A time‐dependent increase in pregenomic RNA and efficient synthesis of covalently closed circular DNA were detected after infection with the GTC‐d11 virus. The involvement of d11 in the HBV large surface protein in the enhanced infectivity was confirmed by an HBV reporter virus and hepatitis D virus infection system. The binding step of the GTC‐d11 virus onto the cell surface was responsible for this efficient infection. Conclusions: This system provides a powerful tool for studying the infection and propagation of HBV in cell culture and also for developing the antiviral strategy against HBV infection.